2013
DOI: 10.1016/j.marpolbul.2012.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Corals from the Persian/Arabian Gulf as models for thermotolerant reef-builders: Prevalence of clade C3 Symbiodinium, host fluorescence and ex situ temperature tolerance

Abstract: a b s t r a c tCorals in the Arabian/Persian Gulf endure summer temperatures of up to 36°C, making them ideal subjects to study the mechanisms underlying thermal tolerance. Unexpectedly, we found the ''generalist'' Symbiodinium clade C3 to be the prevalent symbiont among seven coral species from Abu Dhabi (UAE) waters. Moreover, C3 represented the only dominant symbiont type in Porites spp. from this region. The ''thermotolerant'' symbionts D1a and C15 were not encountered, indicating that the association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
148
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(161 citation statements)
references
References 62 publications
7
148
0
Order By: Relevance
“…The use of proactive reef management is highly debated and beyond this synthesis (see van Oppen et al, 2015;Oppen et al, 2017), but what is evident from these extreme environments is the presence of corals that have traits highly favorable for future survival. For many environments we still do not know how these traits may be conserved or lost as corals are moved to new environments, however evidence of heritable heat-tolerance and conserved thermal tolerance (Hume et al, 2013) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The use of proactive reef management is highly debated and beyond this synthesis (see van Oppen et al, 2015;Oppen et al, 2017), but what is evident from these extreme environments is the presence of corals that have traits highly favorable for future survival. For many environments we still do not know how these traits may be conserved or lost as corals are moved to new environments, however evidence of heritable heat-tolerance and conserved thermal tolerance (Hume et al, 2013) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Probably the most obvious such case lies in S. thermophilum in the PAG (Hume et al ., 2015, 2016). Porites harbouring this Symbiodinium species were more resilient to heat stress than their Pacific counterparts harboring C15 (Hume et al ., 2013). However, further investigation into this symbiosis has revealed a concordant adaptation to the high salinity of the PAG, deeming it unlikely that its thermal tolerance can be extended beyond its current range (D'Angelo et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The region spanning the 18S, ITS1, 5.8S, ITS2, 28S region of the Symbiodinium spp. ribosomal DNA was amplified by performing a PCR using the primers SYM-VAR-FWD, and SYM-VAR-REV (Hume et al, 2013).…”
Section: Identification Of Algal Symbiontsmentioning
confidence: 99%